Defects in chemically synthesized and thermally processed ZnO nanorods: implications for active layer properties in dye-sensitized solar cells - Das, Partha Pratim; Agarkar, Shruti A.; Mukhopadhyay, Soumita; Manju, Unnikrishnan; Ogale, Satishchandra B.; Devi, P. Sujatha (Inorganic Chemistry, 2014)
We have carried out the effect of post annealing temperatures on the performance of solution-grown ZnO rods as photoanodes in dye-sensitized solar cells. Keeping our basic objective of exploring the effect of native defects on the performance of DSSC, we have synthesized ZnO rods having length in the range of 2-5 mu m by a modified sonication-induced precipitation technique. We performed extensive characterization on the samples annealed at various temperatures and confirmed that annealing at 300 degrees C results in ZnO rods with minimum native defects that have been identified as doubly ionized oxygen vacancies. The electron paramagnetic resonance measurements on the samples, on the other hand, confirmed the presence of shallow donors in the low temperature annealed samples. We also carried out electrochemical impedance measurements to understand the transport properties at different interfaces in the solar cell assembly. We could conclude that solution-processed ZnO rods annealed at 300 degrees C are better suited for fabricating DSSC with improved efficiency (1.57%), current density (5.11 mA/cm(2)), and fill factor (45.29%). On the basis of our results, we were able to establish a close connection between the defects in the metal oxide electron transporting nano system and the DSSC performance.